STRESS RESISTANCE AS A PROFESSIONAL QUALITY OF A SOCIAL WORK SPECIALIST (Psychology Travelogs, 2023)
The article examines the theoretical aspects of the peculiarities of the development of stress resistance as a professional quality of social specialists. The article clarifies the essence of the concepts of "stress", "stress resistance", "coping strategies", "professional stress".The author of the article describes the relationship between the development of stress resistance of specialists and their individual mental processes and qualities, namely: locus of control, level of personal anxiety, level of self-esteem, self-confidence, patience, sociability, obligation, self-control, character accents, etc. The development of stress resistance is also significantly influenced by the peculiarities of a person's cognitive sphere, namely, the level of sensitivity, the ability to analyse one's state, use one's own experience and predict the future.The article examines the peculiarities of the professional activity of social workers and their impact on the development of stress resistance. The article examines the peculiarities of the professional activity of social workers and their impact on the development of stress resistance. The author of the article emphasises that adequate behaviour in stressful situations not only demonstrates the professionalism of a social worker, but also prevents his/her professional deformation and helps to maintain health.Consideration of the theoretical aspects of the research problem allowed the author to conclude that social workers need to use methods of self-regulation of mental states (autogenous training, meditation, psychological training) to relieve mental stress and help them overcome difficult situations that accompany their professional activities.
Keywords: stress; professional stress; stress resistance; social specialists; professional activity